Supervisory energy management of a hybrid battery/PV/tidal/wind sources integrated in DC-microgrid energy storage system - Mohamed S. Soliman (Elsevier, 2021)
With increasing energy prices, nuclear energy concerns, climate changes, and electrical grid losses, the demand to rely on more renewable energy is growing. The majority of people currently prefer to live and work in smart environments, such as smart cities and smart institutions with an integrated smart microgrid. Energy management is a complex topic because a large amount of these smart microgrid systems rely on hybrid energy sources. As a result, a smart energy management controller needs to be created. The current research provides a new energy management control technique for a smart DC-microgrid based on a combined fuzzy logic controller (FLC) and high order sliding mode (HSMC) methods. The hybrid energy provider integrated into the DC-microgrid is made up of a battery bank, wind energy, photovoltaic (PV) energy, and tidal energy source. The new proposed intelligent control is intended to regulate source-side converters (SSCs) in order to capture the maximum energy from hybrid renewable energy sources (wind, tidal and PV) while also improving power quality in the DC-microgrid. To keep the microgrid as cost-effective as feasible, renewable energy sources are prioritized. The suggested controller offers a steady output power and sustained service. From the present simulation results under Matlab/Simulink and the comparative analysis, the proposed controller produces +1.02% wind power, +10% PV power, +100% tidal power, and +8.48% load power over intelligent fractional-order proportional–integral–derivative (PID) and more when compared to the super twisting fractional-order and PID controls. In addition, the suggested controller assures smooth output power and uninterrupted service.